The Impact of Sex and Vascular Risk Factors on Brain Tissue Changes with Aging: Magnetization Transfer Imaging Results of the Austrian Stroke Prevention Study - Ropele, S.; Enzinger, C.; Söllinger, M.; Langkammer, C.; Wallner-Blazek, M.; Schmidt, R.; Fazekas, F. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: Quantitative MR imaging techniques allow detection of subtle tissue changes that occur with brain aging beyond the accumulation of WMH and brain atrophy. To what extent sex and cerebrovascular risk factors impact these changes is largely unknown. We attempted to study these risk factors in the context of the community-based ASPS. MATERIAL AND METHODS: We performed MTI in 328 neurologically asymptomatic ASPS participants (age range, 52–87 years). FLAIR was used to delineate WMH and to define NABT. The MTR was measured globally in NABT by using a histogram analysis technique and focally in WMH. Associations of MTR metrics with sex and a large battery of different cerebrovascular risk factors (age, arterial hypertension, diabetes mellitus, smoking, body mass index, cholesterol and triglyceride levels, glycated hemoglobin, and the presence of cardiac disease) were assessed with univariate and multiple regression analysis. RESULTS: Age was seen to affect all MTR histogram metrics of NABT, and a faster decrease of the MTR peak height occurred in men. Independent associations with MTR metrics were found for arterial hypertension and diabetes mellitus. Besides lesion grade, arterial hypertension was also significantly associated with a lower MTR in WMH. CONCLUSIONS: Microstructural tissue changes of NABT increase with aging and may be more extensive in men. Diabetes mellitus and hypertension appear to add to tissue destruction. The exact mechanisms involved await further clarification. ASPSAustrian Stroke Prevention StudyBMIbody mass indexDTIdiffusion tensor imagingFLAIRfluid-attenuated inversion recoveryFWHMfull width at half maximumHbA1cglycol hemoglobinHDLhigh-density lipoproteinmaxmaximumMTmagnetization transferMTIMT imagingMTRMT ratioNABTnormal-appearing brain tissueWMHwhite matter hyperintensity